Western Adventurers and Male Nurses: Indians, Cholera, and Masculinity in Overland Trail Narratives. Issue 1 (13th December 2017) - Keyes, Sarah
Abstract : While historians have tended to focus on overland emigrants' fears of Indians, the cholera years on the Overland Trail called into question Euro-Americans' preconception that they would die at the hands of so-called savages. The presence of cholera undercut the idea that male Argonauts would assert their masculinity by facing off against aggressive Indians. At the same time, the difficulty of finding appropriate female caregivers forced male emigrants to nurse each other. Emigrants addressed these challenges by describing a flexible, expansive white masculinity. This expansive masculinity helped to solve concerns about the nature of migration to California and about antebellum mobility more generally.